2008
DOI: 10.1083/jcb.200707043
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone regulates spine density via its regulatory role in hippocampal estrogen synthesis

Abstract: Spine density in the hippocampus changes during the estrus cycle and is dependent on the activity of local aromatase, the final enzyme in estrogen synthesis. In view of the abundant gonadotropin-releasing hormone receptor (GnRH-R) messenger RNA expression in the hippocampus and the direct effect of GnRH on estradiol (E2) synthesis in gonadal cells, we asked whether GnRH serves as a regulator of hippocampal E2 synthesis. In hippocampal cultures, E2 synthesis, spine synapse density, and immunoreactivity of spino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 63 publications
5
80
1
Order By: Relevance
“…The data obtained stimulating cells directly with LH further support this hypothesis. The final event of GnRH action is the enhancement of E2 synthesis that is registered after 24, 48, and 72 h. Our results are in agreement with data obtained by Prange-Kiel et al [19] on rat hippocampal slices and primary cells treated with GnRH. In fact also in these rat samples GnRH acts with a bell shaped dose response curve and the final steroid synthesized is estradiol.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The data obtained stimulating cells directly with LH further support this hypothesis. The final event of GnRH action is the enhancement of E2 synthesis that is registered after 24, 48, and 72 h. Our results are in agreement with data obtained by Prange-Kiel et al [19] on rat hippocampal slices and primary cells treated with GnRH. In fact also in these rat samples GnRH acts with a bell shaped dose response curve and the final steroid synthesized is estradiol.…”
Section: Discussionsupporting
confidence: 93%
“…In M17 cells GnRH induces an up-regulation of the LH␤ subunit [17] and LH mediates neuronal pregnenolone production increasing Steroidogenic Acute Regulatory protein (StAR) expression [18]. Moreover, GnRH regulates estrogen synthesis and spine synapse density in rat primary hippocampal cultures [19].…”
Section: Introductionmentioning
confidence: 99%
“…27 GnRH was found to regulate the expression of pre-and post-synaptic markers spinophilin, synaptophisin and Egr1 in neurons obtained from hippocampus. 25,28 Hippocampal GnRHR has been implicated in the regulation of aromatase activity, 28 suggesting that the observed neurotrophic effect of GnRH could be mediated by a possible intervention on local synthesis of estrogen, known to affect synaptogenesis and expression of both spinophilin and synaptophysin. 29 This observation also suggests that estrus cycle -dependent synaptogenesis, occurring in the rat female hippocampus, may be regulated by the cyclic release of hypothalamic GnRH.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that serum levels of estradiol control release of gonadotropin-releasing hormone (GnRH) from the hypothalamus, which in turn stimulates the follicle-stimulating hormone/luteinizing hormone secretion that enhances the synthesis of estradiol in ovarian granulose cells. It has been reported that GnRH receptors are abundant in the hippocampus (Prange-Kiel et al, 2008) and GnRH can also directly stimulate estradiol synthesis in the hippocampus, similar to its effect on granulose cells (Brandt et al, 2013). The mechanism by which MDMA induces greater neurotoxicity in females is likely due to gonadal steroid effects on the serotonergic mechanism through which MDMA acts.…”
Section: Sex Differences In Ecstasy-induced Toxicitymentioning
confidence: 97%